Visual Environment Aspects of Public Building Design for People with Down Syndrome - Chalim, Tania; Hayati, Arina; Defiana, Ima (Indonesian Journal of Disability Studies, 2023)
Down syndrome is a trisomy genetic disorder resulting in cognitive delays in the fetus. Cognitive impairment in Down syndrome affects short-term memory and motor impairment due to the characteristic hypotonia of the muscles. People with Down syndrome tend to be visual learners. Through visuals, they are easier to remember and repeat. Visual memory in Down syndrome is better than auditory memory in receiving information. Therefore, the visual environment aspect is presented as a facility in architectural element designs to improve cognition, memory, and motor skills in the wayfinding orientation stimulus. Aspects of the visual environment are offered to stimulate the sensory vision repeatedly. Sensory architecture has a role in activating the body in receiving information, exploring the world, providing taste, and forming social relationships. This paper aims to discuss the design of the visual environment in stimulating the sensory vision of people with Down syndrome to facilitate wayfinding orientation. Visual environment design through colours, patterns, materials, and light are presented as tools to activate visual understanding in responding to and remembering wayfinding orientations. Aspects of the visual environment are communication and encouraging physical activity for users.